X=-2→y=7(6)^(-2+2)+1=7(6)^0+1=7(1)+1=7+1→y=8; (x,y)=(-2,8)
x=-5→y=7(6)^(-5+2)+1=7(6)^(-3)+1=7/6^3+1=7/216+1=0.0324+1→y=1.0324→(x,y)=(-5,1.0324)
Answer: Graph 3
Answer:
70/3
Step-by-step explanation:
- Multiply: 23*3
- 23*3=69
- Add: 69+1
- 69+1=70
- 70/3
<em>Hope this helped!! :)</em>
<em>Brainliest?!?!</em>
<em>Stay safe and have a wonderful day/afternoon/night!!!</em>
The answer is A
hope you found this usefull
I guess this will be good example of how to do it
5/9 is grater than 7/12. same with 9/12, 6/7, 6/9